2022
DOI: 10.1186/s13052-022-01205-w
|View full text |Cite
|
Sign up to set email alerts
|

The adolescent with obesity: what perspectives for treatment?

Abstract: The dramatic increase in overweight and obesity among children and adolescents has become a major public health problem. Obesity in children and young adults is associated with an increased prevalence of cardiometabolic risk factors. Obesity during adolescence represents a strong predictor of obesity and higher mortality in adulthood. Due to the serious implications of obesity in adolescents, effective treatments are urgently needed. Lifestyle interventions represent the recommended therapy. Nevertheless, real… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
44
0
8

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(52 citation statements)
references
References 69 publications
0
44
0
8
Order By: Relevance
“…The prevalence of obesity is seen in one-third of the entire population, and it increases in all age groups of both sexes ( 2 ). According to the World Health Organization, which defines obesity as a body mass index (BMI) ≥ 30 kg/m 2 , obesity is a 21 st -century epidemic and health risk factor with a prevalence that is rapidly increasing in children and adolescents ( 3 , 4 ).…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of obesity is seen in one-third of the entire population, and it increases in all age groups of both sexes ( 2 ). According to the World Health Organization, which defines obesity as a body mass index (BMI) ≥ 30 kg/m 2 , obesity is a 21 st -century epidemic and health risk factor with a prevalence that is rapidly increasing in children and adolescents ( 3 , 4 ).…”
Section: Introductionmentioning
confidence: 99%
“…Overweight/obesity is a public health problem constituting an independent risk factor for several chronic non-communicable diseases and increased mortality [ 1 , 2 ]. Globally, there has been an increase in obesity and a decline in the underweight: the increase in obesity, including severe obesity, may be linked to increasing social disparities that limit healthy food access for people at the greatest risk of malnutrition [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…In numerous studies, laparoscopic sleeve gastrectomy (SG) and Roux-en-Y gastric bypass (RYGB) are the most common bariatric surgery procedures performed in both adolescent and adult patients [4,[22][23][24]. The Teen Longitudinal Assessment of Bariatric Surgery (Teen-LABS) study reported 3-year mean BMI reductions of 29% with Roux-en-Y gastric bypass and 27% with vertical sleeve gastrectomy among individuals aged 19 years or younger [13].…”
Section: Resultsmentioning
confidence: 99%